Granular cell myoblastoma of the biliary tree. Issue 623 (September 1977) - Savage, A.; Devitt, P.
Abstract : A granular cell myoblastoma of the common bile duct is described which caused episodes of jaundice in a young woman. Histological examination demonstrated a close association of the tumour with nerve fibres, tending to support the theory of origin from Schwann cells. The lesion is benign and after excision carries an excellent prognosis.